1991
DOI: 10.1016/0014-5793(91)80369-e
|View full text |Cite
|
Sign up to set email alerts
|

What is the true ATPase activity of contracting myofibrils?

Abstract: Abbreviurio~r: Sl, myosin subfragment IPublished by Elsevier Science Publishers B. V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 14 publications
6
25
0
Order By: Relevance
“…Our working hypothesis is that fibres contracting rapidly under zero load are modeled by activated myofibrils [3] and isometric fibres by crosslinked myofibrils [5]. Here we have shown that AM" ADP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our working hypothesis is that fibres contracting rapidly under zero load are modeled by activated myofibrils [3] and isometric fibres by crosslinked myofibrils [5]. Here we have shown that AM" ADP.…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been several studies of the myofibrillar ATPases [3][4][5][6][7], these were confned to the early steps of the pathway, i.e. the binding and hydrolysis of ATP (steps 1 and 2 in Scheme 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using this method, myofibril suspensions are rapidly mixed with ATP and then quenched at different times with acid to determine the time course of [P i ] produced by ATP hydrolysis [57,90,92,98].…”
Section: Troponin Regulatory Kineticsmentioning
confidence: 99%
“…Thus, the fragile fatty acid synthetase complex was studied successfully by QF after appropriate measures had been taken [55]. Myofibrils are fibrous structures (typically 1 µm diameter and 30 µm length) that appear not to be damaged when mixed with buffer in a QF apparatus [56] and several studies have been carried out on their ATPases (ref. 57 and references cited therein].…”
Section: Further Qf Studiesmentioning
confidence: 99%